(untitled) (Research, Society and Development, 2022)
The present study analyzed the presence of artifacts in endodontically treated teeth restored with fiberglass posts (FP) cemented with different resin cements by means of cone beam computed tomography (CBCT) in order to evaluate the contrast-to-noise ratio (CNR). A total of 60 mandibular premolars were selected to assemble the phantoms in order to simulate a clinical situation. The teeth were allocated to 6 groups, in which G1, G2 and G3 were endodontically treated teeth restored with FP cemented with Nexus 3, Duo-Link, and Allcem Core resin cements, respectively; G4: endodontically treated teeth restored with FP; G5: teeth treated only endodontically; and G6: healthy teeth. Mean gray scale values were analyzed in the axial images of the cervical, middle and apical thirds of the post length. CNR analysis was conducted on all groups except G5 and G6. There was a statistically significant difference in the mean values of the middle third region regarding the groups analyzed (p=0.026). However, artifacts were observed in all studied groups. The statistical difference observed between the cervical and apical thirds when the groups were evaluated together did not characterize the absence of artifacts between the resin cements, even when only the FP was present. Consequently, the choice of a resin cement might be based on ease of handling, better working time, cost-effectiveness, activation modes, substrate conditions, and clinical aspects. In summary, image quality was found to be compromised by artifacts in the presence of FP through CBCT with or without the resin cements in the root canal.